Language dispute and social change in new multilingual institutions in Chaco (Argentina) - Unamuno, Virginia (2014)
Intercultural bilingual education (IBE) programmes in Latin America pose interesting questions for sociolinguistics, since their implementation interrogates the link between language and the nation resulting from the emergence of nation-states, but also from processes of decolonization. In the case of Argentina, a new legal framework and the recent implementation of new public policies at national and provincial levels have caused key social and linguistic transformations in educational institutions in indigenous contexts. This paper aims to show some current transformations in multilingual management in Chaco?s educational institutions. To do this, I consider the case of public schools, traditionally monolingual in Spanish, to which new actors are incorporated, i.e. Wichi bilingual teachers. Their presence at school and their linguistic practices illustrate the tensions between different language ideologies that coexist today in the Argentinean educational system. As I try to show, bilingualism -as an ideological sign and as symbolic capital- and bilingual practices constitute a contested terrain that can be explored through an ethnographic sociolinguistic approach.